Assessing the Impact of Tidal Waves on Learners' Education of Residents of Some Coastal Communities in the Western Region of Ghana - Prah, Kojo Amuah; Mochiah, James Nweah-Ackah; Duker, Joana (Journal of Education and Practice, 2023)
Purpose: The study aimed at exploring the effects of tidal waves on education of learners of four coastal communities in the Western Region of Ghana. Methodology: The study employed mixed-method design. The target population under study was 268(475) made up of 25 teachers, 240(446) learners and two Circuit Supervisors from Ghana Education Service Shama District and two opinion leaders. The study used a sample of 24 teachers, 208 learners, two GES personnel and opinion leaders employing Krejcie and Morgan Table (1970) for determining sample size. Data was collected using questionnaires. The data for the research questions was analyzed quantitatively and qualitatively and presented using frequency and percentage tables. Findings: The study revealed incidence of tidal waves along the coastal four communities in the Western Region. The study also revealed many and diverse effects of tidal waves on the education of the four coastal communities in the Western region of Ghana. Notable among these are loss of space and destruction of educational infrastructure. The one way ANOVA was used to test hypothesis to establish if there was statistical difference between schools and effects of tidal waves. At p< 0.05 there was significant difference between the four schools and effects tidal waves education. F (3, 204) =5.622, Sig. = .001. Unique Contributions to Theory, Policy and Practice: The study addressed the gaps that exist in available literature on effects of tidal waves on coastal communities leading to vital contributions. First the study expands the limited research on impact of tidal waves on coastal communities. This study is the first to consider the impact of tidal waves on learners' education. Secondary, empirical studies on the impact of tidal waves on learners' education in coastal communities does not exist. Existing research has always focused on general impact of tidal waves on coastal communities. The theoretical lens for the study is the comprehensive theory for disaster management. Most natural disaster management practices are based on this theory. This theory has four distinct components: mitigation, preparedness, response, and recovery. Monitoring and evaluation should form an integral part of this theory and should be considered in all the four components of the theory in managing natural disasters.